2018
DOI: 10.1007/s11356-018-1932-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cu (II) and Ni (II) from aqueous solutions by taro stalks chemically modified with diethylenetriamine

Abstract: Taro stalks (TS) were modified by diethylenetriamine (DETA) to obtain the modified taro stalks adsorbents (recorded as MTSA). This kind of raw material is unprecedented and the method of modification is relatively simple. The physicochemical properties of MTSA were characterized by scanning electron microscope (SEM), FTIR, and zeta potential analyzer. The capacity of MTSA for adsorbing heavy metals under different influencing factors was tested by UV-visible spectrophotometer. The results indicated that the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Although this treatment decreases the hydrochar specific surface due to the treatment abundance in N and other joint minerals [122], this modification noticeably increases the hydrochar's surface electronegativity and allows a more stable values of pH zpc . Lu et al [123] investigated the chemical enhancement of taro stalks hydrochar by using diethylenetriamine molecule as a grafting agent. Results showed an important decrease in the zeta potential (�-20 mV).…”
Section: Organic Modificationmentioning
confidence: 99%
“…Although this treatment decreases the hydrochar specific surface due to the treatment abundance in N and other joint minerals [122], this modification noticeably increases the hydrochar's surface electronegativity and allows a more stable values of pH zpc . Lu et al [123] investigated the chemical enhancement of taro stalks hydrochar by using diethylenetriamine molecule as a grafting agent. Results showed an important decrease in the zeta potential (�-20 mV).…”
Section: Organic Modificationmentioning
confidence: 99%
“…It was observed that the infrared spectroscopy could be used to detect the surface functional groups of the adsorbent . Therefore, as Figure shows, the functional groups of HPMC, MHPMC, and MHPMC-loaded Cr (VI) were characterized by the Fourier infrared spectrometer (FT-IR).…”
Section: Resultsmentioning
confidence: 99%
“…The pH zpc value plays a very important role in adsorption materials, which determines the net electric neutral pH value on the surface of the adsorbent. , Generally, satisfying the pH < pH zpc inequality, the adsorbent surface is positively charged, which is favorable to the adsorption of the negatively charged chromium complex anions as a result of electrostatic attraction. On the contrary, at greater pH values (pH > pH zpc ), the surface of the adsorbent is negative, which leads to a decrease in the adsorption of chromium anions by the adsorbent as a result of electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the overlap and aggregation of the adsorbent during the adsorption process reduce the number of adsorption sites. 22 Considering the changes of adsorption capacity and removal ratio, a lower adsorbent should be selected to prevent the adsorption capacity from being too small and save raw materials. Therefore, the optimal adsorbents for adsorption of Ni 2+ , Cu 2+ , and Cr 6+ were 0.65, 0.50, and 0.40 g, respectively.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%